Deoxynivalenol Has the Capacity to Increase Transcription Factor Expression and Cytokine Production in Porcine T Cells - Vatzia, Eleni; Pierron, Alix; Hoog, Anna Maria; Saalmüller, Armin; Mayer, Elisabeth; Gerner, Wilhelm (Frontiers in Immunology, 2020)
Deoxynivalenol (DON) is a Fusarium mycotoxin that frequently contaminates the feed of farm animals. Pigs with their monogastric digestive system are in particular sensitive to DON-contaminated feed. At high concentrations, DON causes acute toxic effects, whereas lower concentrations lead to more subtle changes in the metabolism. This applies in particular to the immune system, for which immunosuppressive but also immunostimulatory phenomena have been described. Research in human and rodent cell lines indicates that this may be partially explained by a binding of DON to the ribosome and subsequent influences on cell signalling molecules like mitogen-activated protein kinases. However, a detailed understanding of the influence of DON on functional traits of porcine immune cells is still lacking. In this study, we investigated the influence of DON on transcription factor expression and cytokine production within CD4+, CD8+ and γδ T cells in vitro. At a DON concentration, that already negatively affects proliferation after Concanavalin A stimulation (0.8 µM) an increase of T-bet expression in CD4+ and CD8+ T cells was observed. This increase in T-bet expression coincided with elevated levels of IFN-γ and TNF-α producing T-cell populations. Increases in T-bet expression and cytokine production were found in proliferating and non-proliferating T cells, although increases were more prominent in proliferating cell subsets. Differently, IL-17A production by CD4+ T cells was not influenced by DON. In addition, frequencies of regulatory T cells and their expression of Foxp3 were not affected. In γδ T cells, GATA-3 expression was slightly reduced by DON, whereas T-bet levels were only slightly modulated and hence IFN-γ, TNF-α or IL-17A production were not affected. Our results show for the single-cell level that DON has the capacity to modulate the expression of transcription factors and related cytokines. In particular, they suggest that for CD4+ and CD8+ T cells, DON can drive T-cell differentiation into a pro-inflammatory type-1 direction, probably depending on the already prevailing cytokine milieu. This could have beneficial or detrimental effects in ongoing immune responses to infection or vaccination.